PENERAPAN MODEL ALTMAN Z-SCORE DALAM MENGUKUR POTENSI KEBANGKRUTAN (STUDI KASUS PADA PERUSAHAAN PERBANKAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018 & 2019) - Rofinus Leki Rofinus Leki (Jurnal Ilmu Ekonomi dan Bisnis, 2021)
Abstract: This research is a sustainability research, which uses the same non- manufacturing Altman Z-Score model, with the aim of re-examining the financial health sustainability of the four BUMN banks that the author has studied in 2017 and in 2019. The four BUMN banks are Bank Negara Indonesia (Persero) Tbk PT, Bank Rakyat Indonesia (Persero) Tbk. PT, Bank Tabungan Negara (Persero) Tbk PT, Bank Mandiri (Persero) Tbk PT. The results showed that PT. Bank BTN (Persero) Tbk has a Z-score that has improved in 2018 and 2019, compared to previous years, namely in 2014, 2015, 2016, and 2017. Currently PT. Bank BTN (Persero) Tbk., has moved from the potential financial distress into a